Duodenal duplication cyst at the second part of the duodenum with congenital duodenal position anomaly completely resected by laparoscopic partial duodenectomy: a case report - Yoichi Nakagawa; Hiroo Uchida; Satoshi Makita; Takahisa Tainaka; Akinari Hinoki; Chiyoe Shirota; Wataru Sumida; Hizuru Amano; Akihiro Yasui; Yoko Kano; Takuya Maeda; Daiki Kato; et al. (Surgical Case Reports)
Abstract Background Duodenal duplication cysts (DDC) are rare duplications of the alimentary tract. Their treatment depends on their size and location. A radical treatment is total resection, if possible. However, partial excision, puncture, and marsupialization can be selected to prevent surgical injury to the pancreaticobiliary tract despite the risk of recurrence. There are some reports of pancreaticoduodenectomy for DDC because of the risk of recurrent symptoms and malignancy. However, this is considered excessively invasive for DDC, particularly in pediatric cases, because of its extremely low rate of malignancy and high morbidity and mortality rates. We encountered a case of DDC with a congenital duodenal position anomaly occurring in the second part of the duodenum. Taking advantage of the congenital duodenal position anomaly, the DDC was completely resected without injuring the pancreaticobiliary duct. Case presentation A 6-year-old boy was diagnosed with a duodenal duplication cyst with obstruction. There was a congenital duodenal position anomaly. The distal second part of the duodenum was the dorsal side of the proximal second part of the duodenum and ascended upward from the proximal second part of the duodenum. The third and fourth parts of the duodenum ran downward to the left and posterior parts of the portal vein, forming the ligament of Treitz. Complete laparoscopic resection of the duodenal duplication cyst and the second to fourth parts of the duodenum, and duodenojejunostomy with retrocolic reconstruction was performed because the duodenum was easily mobilized to the ligament of Treitz owing to the duodenal position anomaly. The duodenojejunostomy with retrocolic reconstruction achieved a more physiologically normal appearance compared to what would have been achieved with a Roux-en-Y reconstruction. The patient was discharged on postoperative day 12 without any complications. Conclusions The procedure used in this case might not be easily applied in all laparoscopy cases. However, it could be an option for duodenal duplication cysts with congenital duodenal position anomalies.